Otonomi Perempuan dalam Mencapai Aktualisasi Diri Pada Novel Home Sweet Loan Karya Almira Bastari - Putu Debby Yolanda; Wiyatmi Wiyatmi; Ary Kristiyani (Balai Bahasa Provinsi Bali, 2026)
This research aims to examine the manifestations of women’s autonomy and their relationship to the process of self-actualization as represented in the novel Home Sweet Loan by Almira Bastari. The study employs the perspectives of feminist psychology as articulated by Jean Baker Miller and the theory of self-actualization proposed by Abraham Maslow, utilizing a qualitative descriptive method. The primary data source is the 309-page novel Home Sweet Loan. Data were collected through close reading, note-taking, and documentation techniques, and subsequently analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing or verification. Data validity was ensured through semantic validity and intrarater reliability. The findings indicate that women’s autonomy in the novel is reflected in several dimensions: (1) financial autonomy, encompassing the ability to manage personal finances, plan long-term financial goals, and obtain employment and income; (2) relational autonomy, characterized by the awareness to choose and determine an equal partner and to cultivate healthy friendships; (3) decision-making autonomy, including making independent life choices, deciding to own a house, and determining educational paths; (4) emotional autonomy, defined as the capacity to regulate anger and forgive others’ mistakes; and (5) autonomy in resisting discrimination within the family sphere and challenging gender stereotypes imposed upon women. Accordingly, this study concludes that autonomy functions as a key factor enabling urban women to attain holistic self-actualization. AbstrakPenelitian ini bertujuan untuk memahami wujud otonomi perempuan serta keterkaitannya dengan proses aktualisasi diri tokoh dalam novel Home Sweet Loan karya Almira Bastari. Kajian ini menggunakan perspektif psikologi feminis Jean B. Miller dan teori aktualisasi diri Abraham Maslow dengan metode deskriptif kualitatif. Sumber data penelitian adalah novel Home Sweet Loan karya Almira Bastari yang terdiri atas 309 halaman. Data dikumpulkan melalui teknik baca, catat, dan dokumentasi kemudian dianalisis menggunakan model analisis Miles dan Huberman yang meliputi tahap reduksi data, penyajian data, serta penarikan kesimpulan atau verifikasi. Keabsahan data dijamin melalui validitas semantis dan reliabilitas intrater. Hasil penelitian menunjukkan bahwa otonomi perempuan dalam novel tercermin dalam beberapa aspek: (1) otonomi finansial, berupa kemampuan mengelola keuangan pribadi, kemampuan merencanakan finansial jangka panjang, dan kemampuan memperoleh pekerjaan dan penghasilan; (2) otonomi relasional, ditandai dengan kesadaran untuk memilih dan menentukan pasangan yang setara serta menjalin hubungan persahabatan yang sehat; (3) otonomi pengambilan keputusan, mencakup membuat keputusan hidup secara mandiri, keputusan memiliki rumah sendiri, dan menentukan pendidikan; (4) otonomi pengelolaan emosi, yaitu kemampuan mengendalikan amarah dan memaafkan kesalahan orang lain; serta (5) otonomi perlawanan terhadap diskriminasi dalam lingkungan keluarga dan melawan stereotip gender terhadap perempuan. Dengan demikian, penelitian ini menyimpulkan bahwa otonomi merupakan faktor kunci bagi perempuan urban untuk mencapai aktualisasi diri secara utuh.